ACTIVATION OF SINABUNG MOUNT VOLCANIC ASH USING VARIOUS MINERAL ACIDS - Shohihatun Bariyah; Lisnawaty Simatupang (Universitas Negeri Medan, 2021)
The effect of various types of mineral acids in activating the silica of volcanic ash of Mount Sinabung has been carried out. The use of various types of mineral acids is aimed at reducing impurities in the form of metals contained in the ash so that it can increase the SiO2 content in the ash. In the treatment, volcanic ash is prepared beforehand by grinding and sieving with a 200 mesh sieve. The sieved ash was then added with mineral acids, namely HCl, HNO3 and concentrated H2SO4 and heated at 100oC for 2 hours. After that, it was neutralized with distilled water and in an oven at 120oC for 6 hours and characterized using XRF to determine the impurities that had been lost. Based on the results obtained using XRF characteristics, the SiO2 content of volcanic ash activated with HCl was 80,23%, HNO3 was 77,23% and H2SO4 was 76,89%. This shows that activation using HCl is more optimal than using HNO3 and H2SO4.